The Release of Concepticon 3.1. (Computer-Assisted Language Comparison in Practice: Tutorials on Computational Approaches to the History and Diversity of Languages, 2023)
In the Concepticon project, we add more concept lists, improve the links to concept sets, and discuss ambiguous cases regularly. With every new release, the Concepticon is updated and the changes are published. Here, I discuss the improvements we integrated into the newest version: Concepticon 3.1. After covering the new lists that were added to Concepticon in this release, I describe the process of refining concept relations and mappings. I also demonstrate how we deal with inconsistencies in the data we encounter using the example of a wordlist that proved to be inconsistent. The aim is to inform about the processes and discussions that led to the new version of Concepticon.
Keywords: conception; release; overview